2017
DOI: 10.1177/0735633117689892
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Learning and Students’ Perceptions Toward Using Tablets for Learning: The Mediating Role of Perceived Engagement Among High School Students

Abstract: Integrating mobile technology in schools has become a growing trend in recent years. Studies suggest that the use of tablets has potential contributions for learning. The current study explored the use of tablets for learning among 427 high school students, utilizing both qualitative and quantitative methods. The purpose was to assess students' perceptions toward the effectiveness of using tablets in learning and to examine a model in which perceived engagement mediates the effects of content usage types, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
(55 reference statements)
3
20
1
4
Order By: Relevance
“…The positive findings of team perception are in line with Roach [42], who reported that students could benefit a lot from group discussion in a flipped classroom. The positive findings about mobile perception are consistent with previous studies [43,44] but inconsistent with Molina et al [45]. In Lin's study, most students reported positive perceptions toward the usage of mobile interactive learning and the diagnosis system, but Molina concluded that mobile phones were not suitable to access and visualize learning materials, as they imposed an additional cognitive load.…”
Section: Discussion and Limitationssupporting
confidence: 62%
“…The positive findings of team perception are in line with Roach [42], who reported that students could benefit a lot from group discussion in a flipped classroom. The positive findings about mobile perception are consistent with previous studies [43,44] but inconsistent with Molina et al [45]. In Lin's study, most students reported positive perceptions toward the usage of mobile interactive learning and the diagnosis system, but Molina concluded that mobile phones were not suitable to access and visualize learning materials, as they imposed an additional cognitive load.…”
Section: Discussion and Limitationssupporting
confidence: 62%
“…These findings showed that students in the MD scenario had more positive perceptions and fewer negative perceptions than those in the DC scenario. Such results were consistent with those of Soffer and Yaron (2017), which indicated that students generally showed positive attitudes toward mobile learning.…”
Section: An Overviewsupporting
confidence: 89%
“…It is the effort students dedicate to everyday school activities. As mentioned earlier, there is enough evidence that supports the existence of a relationship between student engagement and learning outcomes (Lee, 2014;Soffer & Yaron, 2017).…”
Section: Sns and Students' Engagementmentioning
confidence: 80%